Ignorance - Kundera, Milan 1929-; Asher, Linda (New York : Perennial, 2003)
A man and a woman meet by chance while returning to their homeland, which they had abandoned 20 years earlier when they chose to become exiles. Will they manage to pick up the thread of their strange love story, interrupted almost as soon as it began and then lost in the tides of history?
Keywords: Man-woman relationships -- Fiction -- Fiction; Czech literature